A medicalização dos problemas de comportamento e da aprendizagem : uma prática social de controle - Suzuki, Mariana Akemi (2012)
This study is addressed to the issues related to the medicalization process that has being installed in the current society, more specifically, about the medicalization of school complaints (behavior and learning problems of students in school). It is airned to understand the effects of the medicalization of students in the school routine. More specifically, the objective was to investigate the effects of the process of medicalization of students who exhibit behavior deerned inappropriate by the school team. This is a bibliographic and empirical research. In the bibliographic research we tried to articulate the history of medicalization in the way it has been understood and its implications for the present days, focusing on the school as one of the places where this does occur. The empirical research involved ten teachers that teach classes for students who are rnaking use of medication for showing inappropriate behavior in the school. This research was guided by a historical perspective that comprehends the school cornplaints as a synthesis of multiple social determinations. The theoretical framework for analyzing the information collected was based rnainly on authors who treat the presented subject away from a view of the organicist and biologicist problems in the schooling process, and also by authors who belong to the culturalhistorical psychology because in this theory, the developrnent of the hurnan psyche is explained as deterrnined by historical conditions and by the culture in which the individual belongs, at the sarne time that this psyche detennines such conditions. The results showed that there prevails a naturalized comprehension of the development of the human psyche in school. It is believed that the medicated student can focus more, do the activities in the classroorn, starting to produce satisfactorily. However, one may question the consequences of the rnedicalization to the childhood. Moreover, it is possible to reflect the extent to which the use of drugs for social problems is a justified short-term irnprovernent in concentration and the behavior control of these students. It was picked up a feeling of impotence on the part of the educators that, because of not being able to be active parts in the teaching process, do not consider thernselves capable of influencing in this formation. Thus, they look for alternatives that are presented in the school environment as a solution to behavior problems. The referral to the doctor would be one of such altematives, which was identified as a process of outsourcing the education along capitalist lines. The paradigm that is being built is that the use of psychotropics being increasingly more frequent is an appeal against the problems coming by the modern society. lt is observed that this is a contradiction, since, while the teacher is not inserted in the teaching process, he reaffirms this exclusion understanding that is a medication which will intercede m the student problem. Therefore, the failure to acknowledge the work of the teacher as a mediator between the student and knowledge, appears in an objectified form in the process of medicalization in the modern society.